ANALISIS USAHA DAN PEMASARAN MADU KELULUT DI KABUPATEN KAMPAR - Sisca Vaulina; Sri Ayu Kurniati (DINAMIKA PERTANIAN, 2019)
Bee breeding is a side job and source of income for local population. The research objectives were to analyze the characteristics breeders and business profile of kelulut honey, to know the kelulut honey cultivation technology, recognize the rocessing (agroindustry) of kelulut honey, determine the production costs, production, income, and efficiency of kelulut honey, and analysis the marketing of kelulut honey in Kampar regency. This study used a survey method. The sample was selected by purposive sampling as 26 breeders. Data were analyzed qualitative and quantitative descriptive approaches. The results showed that the characteristics of the breeders were in the productive age category (26-55 years old), SD-Bachelor education and breeding experience between 1-6 years. The business was established in 2016 with the name of “Kelompok Madu Galo-Galo Kuok Lestari”. The breeders have 2-40 bee boxes and use family labor. Technology of breeding kelulut honey consisted of a parent colony, colony splitting, manufacture and placement of hive, maintenance, and harvesting. The processing was traditional. Kelulut honey required a production cost of IDR 487,883.33/production process, produce an average production of 20.04 liters during the flowering season and the non-flowering season 7.79 liters. The average net income derived each harvesting as IDR 2,973,655.13/breeder/boxe and IDR 858,270.52/ breeders/boxe during on flower season and off season, respectively. Kelulut honey marketing only sells to the city of Pekanbaru.